2021
DOI: 10.1016/j.ympev.2021.107300
|View full text |Cite
|
Sign up to set email alerts
|

King or royal family? Testing for species boundaries in the King Cobra, Ophiophagus hannah (Cantor, 1836), using morphology and multilocus DNA analyses

Abstract: In widespread species, the diverse ecological conditions in which the populations occur, and the presence of many potential geographical barriers through their range are expected to have created ample opportunities for the evolution of distinct, often cryptic lineages. In this work, we tested for species boundaries in one such widespread species, the king cobra, Ophiophagus hannah (Cantor, 1836), a largely tropical elapid snake distributed across the Oriental realm. Based on extensive geographical sampling acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 113 publications
0
9
1
Order By: Relevance
“…kaouthia and king cobra ( Ophiophagus hannah ) venoms [ 39 , 40 ]. This finding is expected as the king cobra is classified in a different genus, and it was recently reported that there could be multiple species of king cobra [ 41 ]. Densitogram of N .…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…kaouthia and king cobra ( Ophiophagus hannah ) venoms [ 39 , 40 ]. This finding is expected as the king cobra is classified in a different genus, and it was recently reported that there could be multiple species of king cobra [ 41 ]. Densitogram of N .…”
Section: Discussionmentioning
confidence: 79%
“…Incapability of KCAV in recognizing N. kaouthia venom proteins in western blot is likely to be due to interspecies variation in venom toxin composition between N. kaouthia and king cobra (Ophiophagus hannah) venoms [39,40]. This finding is expected as the king cobra is classified in a different genus, and it was recently reported that there could be multiple species of king cobra [41]. Densitogram of N. sumatrana venom blots that were incubated with NPAV and CAV showed a similar number of peaks, which indicates similar toxin-antibody binding capabilities.…”
Section: Plos Onementioning
confidence: 99%
“…It is conspicuous that the two Asian species ( P. bivittatus and P. brongersmai ) have the highest levels of positive charges within the orthosteric site, which suggests a stronger predatory pressure. While Naja (cobra) species are widespread snake-eating predators in both Africa and Asia, the much larger snake-eating predators in the Ophiophagus genus are only found in Asia [ 41 ]. The giant species P. sebae reaches sizes > 7 m and would therefore soon outgrow the prey size range of <2 m Naja species; the equally massive P. bivittatus would be in the prey size range of Ophiophagus species.…”
Section: Resultsmentioning
confidence: 99%
“…Genetic differentiation among V. bengalensis and other monitor lizard species from mitochondrial genes and microsatellite loci. level of morphological divergence (Shankar et al, 2021). Several phylogenetic studies on birds (Johansson et al, 2007;Martens et al, 2011), insects (Schmidt et al, 2012), amphibians (Hofmann et al, 2017) and reptiles (Xu et al, 2021) provide information and understanding regarding divergence in the Himalayan biota.…”
Section: Discussionmentioning
confidence: 99%
“…The diversification within Cyrtodactylus allowed exploration of the India–Asia collision and provided insights into Himalayan biogeography (Agarwal et al., 2014). Another example of intraspecific differentiation is in the wide‐ranging king cobra, with four independently evolving genetic lineages yet a low level of morphological divergence (Shankar et al., 2021). Several phylogenetic studies on birds (Johansson et al., 2007; Martens et al., 2011), insects (Schmidt et al., 2012), amphibians (Hofmann et al., 2017) and reptiles (Xu et al., 2021) provide information and understanding regarding divergence in the Himalayan biota.…”
Section: Discussionmentioning
confidence: 99%